Terminal freeze - Child, Lincoln (Child, Lincoln. Jeremy Logan series., 2009)
A group of scientists undertake an expedition to Alaska's Federal Wilderness Zone to study the effects of global warming. The expedition changes suddenly on a routine foray into a glacial ice cave, where the group makes an astonishing find.